The ProVention Consortium - Independent Evaluation Group (Washington, DC: World Bank, 2015)
The provention consortium was created in February 2000 as a formal partnership between the World Bank, other International Financial Institutions (IFIs), bilateral donor organizations, the insurance sector, the academic community, and civil society. Designed as a think-tank to commission research and to disseminate risk reduction tools, the provention secretariat was to rotate from one partner organization to another. Thus, after three years at the Bank, the secretariat was transferred to the International Federation of the Red Cross and Red Crescent Societies (IFRC) in Geneva. The overall goal of provention is to reduce the social, economic, and environmental impacts of natural disasters on vulnerable populations in developing countries in order to alleviate poverty and contribute to sustainable development. This is achieved through (a) forging partnerships; (b) promoting policy; (c) improving practice; and (d) sharing knowledge. Under the Washington-based Secretariat, provention supported four types of activities: applied research studies, pilot and demonstration projects, education and training activities, and workshops and conferences. Provention was repeatedly criticized for its weak governance structure. Therefore, the secretariat commissioned a governance review in 2005. The governance review recommended reactivating the presiding council (PC); replacing the Steering Committee (SC) by a forum to discuss the impact of disasters in developing countries; and creating an Advisory Committee as the main governing body.